Exploring the Evolution of Nursing Procedurals Skills, Mastery, and Competence Through Online Learning Among Students: A Qualitative Study - Gizell Green (SAGE Publishing, 2024)
Introduction Online learning has changed the educational environment and may influence the development of nursing skills, mastery, and competence in students. Objective The study aimed to investigate how nursing students acquire procedural skills, achieve mastery, and build competence through online learning, considering the growing use of technology in healthcare education. Methods This study utilized a qualitative descriptive research approach to investigate the experiences of 32 nursing students from the Nursing Department who had undergone online procedural learning. Semistructured interviews were conducted to collect in-depth insights. Purposive sampling was used to gather data with a profound understanding of the phenomenon. The data analysis encompassed a methodical content analysis coding procedure. Independent researchers reviewed the results to validate the findings. Results Content analysis of the data identified three key themes: achieving nursing procedural knowledge through online learning, achieving nursing procedural skills with the power of online learning, and gaining procedural competence through online social and collaborative learning. Conclusions Online learning played a significant role in shaping and enhancing nursing procedural knowledge, skills, and competence, emphasizing the importance of integrating technology training modules and staying updated with emerging technologies.